Green Algae to Green Fuel: Optimizing the Composition of Bio-Oil Additive Mixture from the Pyrolysis Process and RON 90 for Enhanced Engine Performance - Amrullah, Apip; Irawansyah, Herry; Ghofur, Abdul; Subagyo, Rachmat; Mahmud, Rizal; Farobie, Obie (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2024)
This study explores the optimization of bio-oil additives derived from the pyrolysis of Ulva lactuca algae, blended with RON 90 gasoline to enhance engine performance and reduce emissions. Addressing the urgent need for sustainable energy, the research focuses on a relatively unexplored area—using algae-derived bio-oils in gasoline engines. The study aimed to identify the optimal blend ratio of bio-oil and gasoline to improve engine metrics such as brake specific fuel consumption (BSFC), thermal efficiency, and volumetric efficiency, while minimizing emissions like CO, CO2, and NOx. Experiments were conducted with bio-oil blended at 5%, 10%, and 15% by volume with RON 90 gasoline in a single-cylinder gasoline engine. Results showed that increasing bio-oil concentration led to improved fuel efficiency and thermal efficiency, along with significant reductions in CO and HC emissions. However, NOx emissions presented a complex trend, increasing at lower bio-oil ratios but decreasing significantly at the highest concentration. These findings suggest that algae-derived bio-oil can effectively enhance gasoline engine performance and reduce environmental impact, offering a novel, sustainable alternative fuel option. The study underscores the importance of optimizing blend ratios to maximize benefits and manage emissions, contributing valuable insights to sustainable energy research.